Calcinosis cutis in the auricle: a case report - ATALAY, Fatma; TOPAL, Kübra; KARS, Ayhan (MediHealth Academy, 2022)
Calcinosis cutis is a rare condition defined as the pathological accumulation of amorphous insoluble calcium salts in cutaneous and subcutaneous tissue. There are four subtypes - dystrophic, idiopathic, metastatic, and iatrogenic calcification. The dystrophic form is the most common type of calcinosis cutis, the major agent being trauma. Serum calcium and phosphorus values are within normal limits in these patients. The clinical manifestation generally involves small white papules, and subcutaneous nodules or plaques. The first choice in the treatment of calcinosis cutis is surgery. Surgical procedures have been recommended as the first and most effective option in almost all cases in the literature. We report a case of a patient presenting with growing, painless swelling following trauma to the auricle of the ear identified as dystrophic calcinosis cutis following surgical excision.
Keywords: 3. Good health